Nano ceramic particle reinforced copper-based composite material and preparation method thereof

By adding prefabricated reinforcement bodies in batches and mechanical stirring, the nanoceramic particles are uniformly distributed in the copper base, solving the problem of uniform dispersion of nanoceramic particles in the copper base, and achieving efficient, uniform dispersion and performance improvement.

CN119433279APending Publication Date: 2025-02-14MCC KUNYUAN (CHONGQING) METAL MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411509366.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the stirring casting process, it is difficult to disperse uniformly in the copper matrix, especially when the density difference is large, defects such as settlement and pores are prone to occur, which affects the performance of the composite material.

Method used

The nanoceramic particles are uniformly distributed in the copper base by adding prefabricated reinforcement bodies in batches and mechanical stirring. The specific steps include preheating the nanoceramic particles and coating the copper foil, adding them to the copper melt in batches, and ensuring uniform dispersion through mechanical stirring and vertical continuous casting processes.

Benefits of technology

The efficient and uniform dispersion of nanoceramic particles in copper-based composite materials is achieved, and the mechanical properties and overall performance of the composite materials are improved, while avoiding the occurrence of defects such as pores, improving production efficiency and yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433279A_ABST
    Figure CN119433279A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal-based composite materials, and relates to a nano ceramic particle reinforced copper-based composite material and a preparation method thereof. The preparation method comprises the following steps that S1, nano ceramic particles are preheated to remove water vapor of the nano ceramic particles, the nano ceramic particles are divided into a plurality of parts, each part of the nano ceramic particles is coated with copper foil, and a plurality of parts of prefabricated reinforcements are obtained; s2, protective gas is introduced into the crucible, copper particles are put into the crucible, and high-temperature smelting is conducted to obtain copper melt; s3, adding one part of the prefabricated reinforcement into the copper melt, and uniformly stirring and mixing; s4, the step S3 is repeated until all the prefabricated reinforcements are added into the copper melt, and the prefabricated reinforcements are stirred and mixed to be uniform; and S5, stirring is stopped, a stopper rod at the bottom of the crucible is opened, the continuous casting procedure is started, and the nano ceramic particle reinforced copper-based composite cast ingot is obtained. According to the method, the nano ceramic particles are uniformly distributed in the copper base in a manner of adding the prefabricated reinforcements in batches and mechanically stirring, so that the mechanical property of the composite material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal-based composite materials and relates to a nano-ceramic particle reinforced copper-based composite material and a preparation method thereof. Background Art

[0002] In the field of research and development and preparation of metal matrix composites, the selection of matrix materials and reinforcement materials and their composite effects have always been the focus of research. Among them, wettability has received extensive attention as a key factor in determining whether matrix materials and reinforcement materials can be successfully and easily composited. However, in actual experiments and production processes, in addition to wettability, the density difference between reinforcement and matrix is ​​also an important factor that cannot be ignored.

[0003] Stir casting is a simple, efficient and large-scale production method for producing metal matrix composites. The process involves melting metal, adding reinforcement materials to the melt, and evenly distributing them in the melt by stirring, and finally casting them into a mold for cooling. However, during the melting and casting process, the uniform distribution of particles is affected by many parameters, including the viscosity of the molten metal, the heat transfer rate, the wettability and the stirring method. In particular, when the density difference between the matrix material and the reinforcement material is too large, the reinforcement will tend to settle, which usually requires mechanical stirring and increasing the rotation speed to evenly disperse the reinforcement.

[0004] However, stirring casting faces a series of challenges when it is carried out in an atmospheric environment. High-speed stirring will inevitably introduce air, resulting in defects such as uneven particle distribution and pores. At the same time, the strong centrifugal force generated by high rotation speed may throw the nanoparticles onto the crucible wall, thereby reducing the yield. These problems not only affect the preparation efficiency of the composite material, but also have an adverse effect on its performance.

[0005] In view of the above problems, the present invention proposes a nano-ceramic particle reinforced copper-based composite material and a preparation method thereof. By optimizing the preparation process, the present invention aims to solve the problem of uniform dispersion of the reinforcement in the matrix, while avoiding the generation of defects such as pores, thereby improving the overall performance of the composite material. Summary of the invention

[0006] In view of this, the present invention aims to provide a nano-ceramic particle reinforced copper-based composite material and a preparation method thereof, wherein the nano-ceramic particles are evenly distributed in the copper matrix by adding prefabricated reinforcements in batches and mechanically stirring, so as to effectively improve the mechanical properties of the composite material.

[0007] In a first aspect, the present invention provides a method for preparing a nano-ceramic particle reinforced copper-based composite material, comprising the following steps:

[0008] S1: preheating the nano-ceramic particles to remove moisture, dividing the nano-ceramic particles into several portions, each portion of the nano-ceramic particles is coated with copper foil, and obtaining several portions of prefabricated reinforcements;

[0009] S2: introducing protective gas into the crucible, placing copper particles into the crucible, and melting at high temperature to form a copper melt;

[0010] S3: adding a portion of the prefabricated reinforcement into the copper melt and stirring to mix well;

[0011] S4: repeat step S3 until all prefabricated reinforcements are added to the copper melt and stirred to mix well;

[0012] S5: Stop stirring, open the stopper rod at the bottom of the crucible, start the continuous casting process, and obtain a nano-ceramic particle reinforced copper-based composite ingot.

[0013] Optionally, the nano-ceramic particles are one of HfC, TaC, and WC.

[0014] Optionally, the particle size of the nano-ceramic particles is 50 to 300 nm.

[0015] Optionally, in step S1, the temperature of preheating the nano-ceramic particles is 150-300°C.

[0016] Optionally, in step S1, the nano-ceramic particles are divided into 3 to 8 equal parts by mass.

[0017] Optionally, in step S2, the copper-based smelting temperature is 1300-1400°C.

[0018] Optionally, in steps S3 and S4, the stirring speed is 100-250 rpm, and the stirring time is 5-15 min.

[0019] Optionally, in step S3, the stirring speed is 200 rpm and the stirring time is 5 min.

[0020] Optionally, in step S4, the stirring speed is 150 rpm and the stirring time is 10 min.

[0021] Optionally, the crucible is a cylindrical high-purity graphite crucible with a diameter of D and a height of H. In steps S3 and S4, the stirring rod used for stirring is a four-blade high-purity graphite stirring rod with a stirring diameter of 0.4D, a blade width of 0.15D, and an inclination angle of 45° relative to the horizontal plane.

[0022] Optionally, in steps S3 and S4, during the stirring process, the distance between the bottom end of the stirring rod and the bottom surface of the crucible is maintained in the range of 0.1 to 0.25H.

[0023] Optionally, in step S5, the speed of continuous casting is 1 to 2.5 mm / s.

[0024] In a second aspect, the present invention also provides a nano-ceramic particle reinforced copper-based composite material prepared according to the above method.

[0025] In a third aspect, the present invention further provides a copper alloy product, which is mainly made of the above-mentioned nano-ceramic particle reinforced copper-based composite material.

[0026] The beneficial effects of the present invention are:

[0027] First, the present invention divides nano-ceramic particles into several parts, and forms several prefabricated reinforcements by coating with copper foil to increase the density, thereby avoiding the floating phenomenon of nano-ceramic particles in copper melt. Moreover, if the nano-ceramic particles are directly put into the copper melt, they may not be completely wetted by the copper melt due to the small size and special surface properties of the nano-particles. This phenomenon of incomplete wetting will seriously hinder the uniform dispersion of the nano-ceramic particles in the copper melt, thereby affecting the final performance of the composite material. However, the present invention pre-coats the nano-ceramic particles in copper foil, and the copper foil, as a densely arranged body of copper atoms, has excellent wettability with the copper melt. When the nano-ceramic particles coated with copper foil enter the copper melt, the copper foil gradually dissolves in the high-temperature copper melt, releasing the nano-ceramic particles. Due to the good wettability between the copper foil and the copper melt, the nano-ceramic particles can be more easily wetted by the melt during the release process, and are evenly dispersed by the flow and stirring of the copper melt.

[0028] On this basis, the present invention adopts a method of combining mechanical stirring with vertical continuous casting to achieve efficient and uniform dispersion of nano-ceramic particles in copper melt. By optimizing the stirring parameters, the present invention enables the prefabricated reinforcement to be evenly dispersed in the middle and lower part of the bottom of the copper melt, significantly improving the overall performance of the composite material. In addition, the stirring parameters of the present invention can successfully avoid the introduction of air during high-speed stirring and the problem of nanoparticles being thrown onto the crucible wall, thereby improving the yield of nanoparticles. The vertical casting method isolates the introduction of air, ensuring the purity of the melt and the quality of the composite material.

[0029] It can be seen that the preparation method provided by the present invention can not only obtain a composite material with uniformly dispersed nano-ceramic particles, but also improve the production efficiency and significantly reduce the production cost, thereby providing strong support for the large-scale production of nano-ceramic particle-reinforced copper-based composite materials.

[0030] In addition, the present invention adopts vertical continuous casting to obtain ingots of composite materials and utilizes the rapid cooling technology of the continuous casting crystallizer, which not only ensures that the nanoparticles will not undergo secondary sedimentation during the solidification process, but also helps to maintain the uniform distribution of the nanoparticles in the matrix, and also helps to refine the grains and improve the various properties of the material.

[0031] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0033] Figure 1 A flow chart of a preparation method of a nano-ceramic particle reinforced copper-based composite material provided by the present invention;

[0034] Figure 2 This is the SEM image of the copper-based composite material obtained by the conventional stirring casting method;

[0035] Figure 3 This is a SEM image of the copper-based composite material obtained in Example 1 of the present invention;

[0036] Figure 4 This is a SEM image of the copper-based composite material obtained in Example 2 of the present invention;

[0037] Figure 5 Schematic diagram of the structure of the crucible and stirring rod used in the embodiment of the present invention.

[0038] Reference numerals

[0039] 100-crucible; 200-stirring rod; 210-blade. DETAILED DESCRIPTION

[0040] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0041] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0042] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0043] In the research and development and preparation of metal-based composite materials, stirring casting is used as a simple, efficient and suitable method for large-scale production. The process includes melting the metal, adding reinforcements and stirring evenly, and finally casting and cooling. However, in this process, the uniform distribution of particles is affected by many parameters, such as the viscosity of the molten metal, the heat transfer rate, wettability and stirring method. Especially when the density difference is large, the reinforcement is easy to settle, and it is necessary to increase the speed through mechanical stirring to evenly disperse it. However, stirring casting in an atmospheric environment faces challenges: high-speed stirring can easily introduce air, resulting in defects such as uneven particle distribution and pores; the centrifugal force generated by high speed may throw out nanoparticles and reduce the yield. For example Figure 2 As shown, the copper-based composite material obtained by ordinary stirring casting method has obvious agglomeration of nano-ceramic particles.

[0044] Based on this, the present invention proposes a method for preparing a nano-ceramic particle reinforced copper-based composite material, such as Figure 1 As shown, the preparation method comprises the following steps:

[0045] S1: preheating the nano-ceramic particles to remove moisture, dividing the nano-ceramic particles into several portions, each portion of the nano-ceramic particles is coated with copper foil, and obtaining several portions of prefabricated reinforcements;

[0046] S2: introducing protective gas into the crucible, placing copper particles into the crucible, and melting at high temperature to form a copper melt;

[0047] S3: adding a portion of the prefabricated reinforcement into the copper melt and stirring to mix well;

[0048] S4: repeat step S3 until all prefabricated reinforcements are added to the copper melt and stirred to mix well;

[0049] S5: Stop stirring, open the stopper rod at the bottom of the crucible, start the continuous casting process, and obtain a nano-ceramic particle reinforced copper-based composite ingot.

[0050] Specifically, in an embodiment of the present invention, the nano-ceramic particles are one of HfC, TaC, and WC, and the particle size of the nano-ceramic particles is 50-300 nm.

[0051] Specifically, in the embodiment of the present invention, in step S1, the temperature of preheating the nano-ceramic particles is 200°C.

[0052] Specifically, in an embodiment of the present invention, in step S1, the nano-ceramic particles are divided into 3 to 8 equal portions by mass, and the specific number of portions depends on the type of the nano-ceramic particles.

[0053] Specifically, in an embodiment of the present invention, in step S2, the smelting temperature of the copper base is 1300-1400°C.

[0054] Specifically, in the embodiment of the present invention, in steps S3 and S4, the stirring speed is 100-250 rpm, and the stirring time is 5-15 min.

[0055] Specifically, in an embodiment of the present invention, Figure 5 As shown, the crucible 100 is a cylindrical high-purity graphite crucible with a diameter of D and a height of H. In steps S3 and S4, the stirring rod 200 used for stirring is a four-blade high-purity graphite stirring rod with a stirring diameter of 0.4D, a blade 210 width of 0.15D, and an inclination angle of the blade 210 relative to the horizontal plane of 45°.

[0056] Specifically, in the embodiment of the present invention, in steps S3 and S4, during the stirring process, the distance between the bottom end of the stirring rod and the bottom surface of the crucible is maintained in the range of 0.1 to 0.25H.

[0057] Specifically, in an embodiment of the present invention, in step S5, the speed of continuous casting is 1-2.5 mm / s.

[0058] An embodiment of the present invention also provides a nano-ceramic particle reinforced copper-based composite material prepared according to the above method.

[0059] An embodiment of the present invention further provides a copper alloy product, which is mainly made of the above-mentioned nano-ceramic particle reinforced copper-based composite material.

[0060] Example 1

[0061] A method for preparing a nano-ceramic particle reinforced copper-based composite material, wherein the nano-ceramic particle is TaC, specifically comprising the following steps:

[0062] (1) Weighing 135 g of TaC particles with a particle size of 200 nm, drying the TaC particles in a drying oven at 200° C., and then dividing the particles into four equal parts, each of which is coated with copper foil to obtain four Cu-TaC prefabricated reinforcements;

[0063] (2) introducing argon gas into a high-purity graphite crucible, adding 2000 g of copper particles into the high-purity graphite crucible, smelting the copper particles at high temperature until they are completely melted into a copper melt, and keeping the temperature at 1350° C.;

[0064] (3) Add a portion of Cu-TaC prefabricated reinforcement into a high-purity graphite crucible, turn on the mechanical stirring device, lower the high-purity graphite stirring rod to 2 cm from the bottom of the crucible, and stir at 200 rpm for 5 min;

[0065] (4) Add the remaining Cu-TaC prefabricated reinforcements one by one according to step 3 and stir. After all the Cu-TaC prefabricated reinforcements are added, stir at 150 rpm for 10 min;

[0066] (5) Stop stirring, open the stopper rod at the bottom of the high-purity graphite crucible, start the continuous casting crystallizer, and pull the embryo at a speed of 1 to 2.5 mm / s to obtain a Cu-TaC composite ingot.

[0067] The cylindrical high-purity graphite crucible used in this embodiment has a diameter of D and a height of H. The four-blade high-purity graphite stirring rod used in this embodiment has a stirring diameter of 0.4D, a blade width of 0.15D, and an inclination angle of 45° relative to the horizontal plane. During the stirring process, the distance between the high-purity graphite stirring rod and the bottom surface of the crucible is kept no more than half of the height of the crucible.

[0068] The scanning electron microscope observation results of the titanium carbide reinforced aluminum matrix composite material prepared in this embodiment are as follows: Figure 3 As shown, it can be seen that there is no obvious agglomeration of tantalum carbide particles on the Cu surface.

[0069] Example 2

[0070] A method for preparing a nano-ceramic particle reinforced copper-based composite material, wherein the nano-ceramic particle is TaC, specifically comprising the following steps:

[0071] (1) Weighing 280 g of TaC particles with a particle size of 200 nm, drying the TaC particles in a drying oven at 200° C., and dividing them into 6 portions after drying, each of which is coated with copper foil to obtain 6 portions of Cu-TaC prefabricated reinforcements;

[0072] (2) introducing argon gas into a high-purity graphite crucible, adding 2000 g of copper particles into the high-purity graphite crucible, smelting the copper particles at high temperature until they are completely melted into a copper melt, and keeping the temperature at 1350° C.;

[0073] (3) Add a portion of Cu-TaC prefabricated reinforcement into a high-purity graphite crucible, turn on the mechanical stirring device, lower the high-purity graphite stirring rod to 2 cm from the bottom of the crucible, and stir at 200 rpm for 10 min;

[0074] (4) adding the remaining Cu-TaC prefabricated reinforcements one by one according to step 3 and stirring; after all the Cu-TaC prefabricated reinforcements are added, stirring is performed at a speed of 150 rpm for 15 minutes;

[0075] (5) Stop stirring, open the stopper rod at the bottom of the high-purity graphite crucible, start the continuous casting crystallizer, and pull the embryo at a speed of 1 to 2.5 mm / s to obtain a Cu-TaC composite ingot.

[0076] The cylindrical high-purity graphite crucible used in this embodiment has a diameter of D and a height of H. The four-blade high-purity graphite stirring rod used in this embodiment has a stirring diameter of 0.4D, a blade width of 0.15D, and an inclination angle of 45° relative to the horizontal plane. During the stirring process, the distance between the high-purity graphite stirring rod and the bottom surface of the crucible is kept no more than half of the height of the crucible.

[0077] The scanning electron microscope observation results of the titanium carbide reinforced aluminum matrix composite material prepared in this embodiment are as follows: Figure 3 As shown, it can be seen that the tantalum carbide particles are evenly distributed on the Cu surface without obvious agglomeration.

[0078] Pure copper was used as a comparative sample, and the composite material prepared in Example 1 and the composite material prepared in Example 2 were used as experimental samples. The hardness and electrical conductivity thereof were tested respectively. The results are shown in Table 1.

[0079] Table 1

[0080] Material Type Hardness (HV) Conductivity (%IACS) Pure Copper 48.34 100.2 Example 1 68.42 74.3 Example 2 83.52 68.5

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a nano-ceramic particle reinforced copper-based composite material, characterized in that: The following steps are involved: S1: preheating the nano-ceramic particles to remove moisture therefrom, dividing the nano-ceramic particles into several portions, each portion of the nano-ceramic particles being coated with copper foil to obtain several portions of prefabricated reinforcements; S2: introducing a protective gas into the crucible, placing copper particles into the crucible, and melting at high temperature to form a copper melt; S3: adding a portion of the prefabricated reinforcement into the copper melt and stirring to mix well; S4: repeating step S3 until all the prefabricated reinforcements are added to the copper melt and stirred to mix well; S5: stopping stirring, opening the stopper rod at the bottom of the crucible, and starting the continuous casting process to obtain an ingot of nano-ceramic particle reinforced copper-based composite material.

2. The preparation method according to claim 1, characterized in that: The nano ceramic particles are one of HfC, TaC and WC.

3. The preparation method according to claim 1, characterized in that: The particle size of the nano ceramic particles is 50-300 nm.

4. The preparation method according to claim 3, characterized in that: In step S1, the temperature of preheating the nano ceramic particles is 150-300°C.

5. The preparation method according to claim 1, characterized in that: In step S1, the nano-ceramic particles are divided into 3 to 8 equal parts by mass.

6. The preparation method according to claim 1, characterized in that: In step S2, the copper base is smelted at a temperature of 1300-1400°C.

7. The preparation method according to claim 1, characterized in that: In steps S3 and S4, the stirring speed is 100-250 rpm, and the stirring time is 5-15 min.

8. The preparation method according to claim 1, characterized in that: The crucible is a cylindrical high-purity graphite crucible with a diameter of D and a height of H. In steps S3 and S4, the stirring rod used for stirring is a four-blade high-purity graphite stirring rod with a stirring diameter of 0.4D, a blade width of 0.15D, and an inclination angle of 45° relative to the horizontal plane.

9. The preparation method according to claim 8, characterized in that: In steps S3 and S4, during the stirring process, the distance between the bottom end of the stirring rod and the bottom surface of the crucible is maintained in the range of 0.1 to 0.25H.

10. The preparation method according to claim 1, characterized in that: In step S5, the speed of continuous casting is 1 to 2.5 mm / s.

11. A nano-ceramic particle reinforced copper-based composite material prepared by the method according to any one of claims 1 to 10.

12. A copper alloy product, characterized in that: The copper alloy product is mainly made of the nano-ceramic particle reinforced copper-based composite material described in claim 11.